Research and teacher self-inquiry reawaken learning. (February 2015) - Blumenreich, Megan; Falk, Beverly
This article reports on a study of teachers who have engaged in systematic research about their practice. It describes the inquiries of two urban teachers into challenges and dilemmas common to many who work with diverse groups of students. The accounts presented reveal how teachers are able to construct new knowledge about teaching when they engage as inquirers about their work; they invent new solutions to nagging problems, identify new challenges that need to be addressed, and respond to the unique contexts and needs of the children and families of the communities in which they teach.